Comparison of the efficacy and safety in the treatment strategies between chemotherapy combined with antiangiogenic and with immune checkpoint inhibitors in advanced non-small cell lung cancer patients with negative PD-L1 expression: A network meta-analysis - Li, Jiaqi; Chen, Yingjie; Hu, Fan; Qiang, Huiping; Chang, Qing; Qian, Jialin; Shen, Yinchen; Cai, Yong; Chu, Tianqing (Frontiers in Oncology, 2022)
Background: In the first-line treatment of advanced non–small cell lung cancer (NSCLC), for those patients with negative PD-L1 expression, which treatment strategy has the better efficacy and safety between chemotherapy combined with antiangiogenic or with immune checkpoint inhibitors (ICIs) is still unclear due to the absence of head-to-head clinical trials. This study aims to answer the question by performing a systematic review and network meta-analysis (NMA). Methods: Electronic databases (PubMed, Embase, Cochrane Library, Web of Science, and ClinicalTrials.gov) were systematically searched according to extract eligible from inception to October 2022, as well as the abstracts from the most recent main oncology congresses (AACR; ASCO; WCLC; ESMO). Overall survival (OS), progress-free survival (PFS), and adverse events (AEs) of grades 3 to 5 were independently extracted and collected by two reviewers based on the PRISMA guideline. We used Cochrane’s risk of bias tool for randomized controlled trials through RevMan 5.3 to ascertain the quality of the included studies. NMA with a Bayesian random effect model was performed by R (version 4.0.4). Results: According to the ranking list from OS-NMA, pembrolizumab combined with chemotherapy has the most effective ranking first(SUCRA=0.809844) (pooled HR=0.65[0.51-0.83]). On PFS, the triple combination of nivolumab /bevacizumab/chemotherapy ranks first (NMA estimate: HR=0.35[0.28-0.43]). On safety, in combination with chemotherapy, sintilimab has minimal toxicity, followed by pembrolizumab+chemo. Conclusions: In advanced NSCLC patients with negative PD-L1 expression, pembrolizumab + chemo ranks first in the efficacy of OS and doesn’t apparently increase the incidence of any grade≥3 AE compared with chemo alone. On PFS, pembrolizumab also has advantages, but for patients with squamous cell carcinoma, camrelizumab+chemo seems to be a better choice. Systematic review registration: PROSPERO CRD 42021231441.